ENGLISH TEACHING METHODS - Otamirzayeva , Maftuna Azamat qizi (Educational Research in Universal Sciences, 2024)
There are different ways to teach English. teaching a foreign language,It is necessary to pay attention to new ways of stimulating students’ speech. However, many classical schools still try to teach using old methods and old books. There are always problems and you never speak English Good. Using new methods, you can easily learn to speak English and improve it. You can speak like a native speaker.